Chrysomeloidea II (Orsodacnidae, Megalopodidae, Chrysomelidae) - Part 2 : Updated and Revised Second Edition - Bezdek, Jan,; Sekerka, Lukáš, (Catalogue of Palaearctic Coleoptera ;, 2024)
Volume 6/2 of the Catalogue of Palaearctic Coleoptera focuses on the second part of the beetle superfamily Chrysomeloidea reported from the Palaearctic biogeographic region. For the genus and species-groups taxa all relevant names are given and